WORLD WAR II 'VON UNTEN': CHILDHOOD AND YOUTH IN LISA TETZNER'S IST PAUL SCHULDIG? (1945)*. (October 2016) - Pinfold, Debbie
ABSTRACT: Literary presentations of children in war tend to depict them exclusively as innocent victims. Indeed, even those texts featuring children who have been subjected to, and have ostensibly absorbed, Nazi indoctrination continue to insist on a Romantic myth of childhood as the embodiment of a prelapsarian past and redemptive potential for the future. This essay, however, focuses on the way the exiled author Lisa Tetzner (1894–1963) uses images of childhood to negotiate concepts of guilt and responsibility in her novel for younger readers, Ist Paul schuldig? (1945), the seventh volume of her series Die Kinder aus Nr. 67 . It will argue that the novel anticipates debates about German guilt first fully articulated in Karl Jaspers's Die Schuldfrage (1946), as well as later debates about German wartime suffering. It will further suggest that by focusing on the moral guilt of an individual adolescent whose childhood backstory is very familiar to the reader, the novel creates a challenging and yet sympathetic space where not only youthful German readers might have explored the extent of their personal responsibility for the Third Reich in 1945. Literarische Kriegskinder werden zum großen Teil als ausschließlich unschuldige Opfer dargestellt. Auch in Texten, in denen Kinder der nationalsozialistischen Ideologie ausgesetzt werden und diese scheinbar übernehmen, wird ein romantischer Mythos von Kindheit als Verkörperung einer ursprünglichen Unschuld und eines erlösenden Zukunftspotenzials aufrechterhalten. Dieser Aufsatz aber analysiert Ist Paul schuldig? (1945), den siebten Band der Jugendromanserie Die Kinder aus Nr. 67, in dem die Exilautorin Lisa Tetzner (1894–1963) Kindheitsbilder benutzt, gerade um sich mit Vorstellungen von Schuld und Verantwortung auseinanderzusetzen. Es wird argumentiert, dass dieser Roman sowohl Debatten über deutsche Schuld vorwegnimmt, die zum ersten Mal in Karl Jaspers Die Schuldfrage (1946) ausführlich dargelegt wurden, als auch spätere Debatten über deutsches Kriegsleiden. Ferner wird argumentiert, dass Tetzner durch ihre Beschreibung der moralischen Schuld eines einzelnen Heranwachsenden, dessen Kindheitsgeschichte dem Leser vertraut ist, nicht nur jugendlichen Lesern einen relativ geschützten Raum bietet, sich 1945 offen mit dem Ausmaß ihrer persönlichen Verantwortung für die Ereignisse des Dritten Reiches auseinanderzusetzen.